Push‐out bond strength of an experimental self‐adhesive resin cement. (12th November 2012) - Juloski, Jelena; Fadda, Giovanni M.; Radovic, Ivana; Chieffi, Nicoletta; Vulicevic, Zoran R.; Aragoneses, Juan M.; Ferrari, Marco
Abstract : The adhesion of fiber posts luted with simplified adhesive systems has been a matter of great interest over the past years. The aim of this study was to assess the post retentive potential of experimental self‐adhesive resin cement (EXP) when used alone and in combination with a self‐etch adhesive. Fiber posts were placed in endodontically treated teeth and divided into four groups ( n = 6) according the luting material, as follows: group 1 (EXP alone); group 2 (EXP used with self‐etch adhesive); group 3 (marketed dual‐cured cement used with self‐etch adhesive); and group 4 (marketed self‐adhesive cement). The push‐out test was used to assess the retentive strength of fiber posts (expressed in MPa), and specimens were analyzed under a stereomicroscope to determine failure mode. The adhesive interface between the cement and root canal dentin for each group was evaluated using scanning electron microscopy. The post retentive potential of group 1 (EXP) (7.48 ± 4.35 MPa) was comparable with that of marketed cements from group 4 (6.79 ± 3.68 MPa) and group 3 (8.77 ± 4.58 MPa). When EXP was used in combination with self‐etch adhesive (group 2), significantly higher push‐out bond‐strength values were measured (15.87 ± 4.68 MPa) compared with the other groups.